Parenting Practices and Psychosomatic Complaints Among Swedish Adolescents - Karina Grigorian; Viveca Östberg; Jonas Raninen; Jonas Raninen; Sara Brolin Låftman (Frontiers Media S.A., 2023)
Objectives: Parent-adolescent relationships play a crucial role in youth development. This study examines the associations between parenting practices (parental support, knowledge, and rule-setting) and psychosomatic complaints across middle and late adolescence.Methods: The study utilised data from a Swedish national cohort (n = 3,678). Participants completed self-report questionnaires in 2017 (∼15-16 years) and again in 2019 (∼17-18 years).Results: Parental support exhibited the strongest and most consistent inverse cross-sectional associations with psychosomatic complaints during both middle and late adolescence. Furthermore, increases in parental support and parental knowledge were associated with decreases in adolescent psychosomatic complaints. However, parental support and knowledge at age 15-16 were not prospectively associated with psychosomatic complaints at age 17-18.Conclusion: These findings underscore the importance of ongoing parental engagement, particularly in terms of providing constant support, throughout middle and late adolescence.